Patterns of Social Interaction Between Muslims in Diversity - Sultony, Ahmad; Syukur, Abdul (Alfuad: Jurnal Sosial Keagamaan, 2025)
The purpose of this article is to examine the pattern of social interaction among Muslims in religious plurality in Salatiga Permai Housing in Salatiga City, Candirejo Housing in Jombor Village, Tuntang Sub-district, Semarang Regency, and Perumnas Banyumanik in Semarang City, and the factors that strengthen social integration. This research uses a qualitative approach of case study type. Data collection techniques used interviews, observation, and documentation. This research uses descriptive analysis and explanatory analysis. The pattern of social interaction between Muslims in religious plurality in the three housing estates is peaceful by promoting human values that emphasise the value of mutual respect, respect and uphold the values of togetherness. Factors that strengthen social integration include the expertise of the leaders in each place in managing and ÔÇÿtreatingÔÇÖ differences to be processed into values that are beneficial to the establishment and continuity of life together. The expertise of these leaders is determined by their educational background, their perspective on religious teachings and their socio-economic capabilities.